2006
DOI: 10.1080/17453670610013286
|View full text |Cite
|
Sign up to set email alerts
|

Reindeer BMP extract in the healing of critical-size bone defects in the radius of the rabbit

Abstract: Background Native BMP extracts from reindeer effectively induce ectopic new bone formation in vivo, but their bone healing properties have not yet been evaluated. We investigated the effect of reindeer BMP extracts on the healing of long bone defects.Methods The implants tested contained 5 mg or 10 mg of unsterilized BMP extract from reindeer and 10 mg of gamma-sterilized BMP extract administered with collagen carrier (Lyostypt, B. Braun, Germany). 70 µg of rhBMP-2 with collagen carrier (InductOs; Wyeth Europa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…The 10 mg of bone extract group had significantly higher mean stiffness than the collagen group [9]. Our results confirm previous results, which showed that reindeer bone extract has good osteoconductivity both in [5,6,9]. It is known that the animal and fracture models, delivery systems and route of administration influence the dose response in bone healing studies [16].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The 10 mg of bone extract group had significantly higher mean stiffness than the collagen group [9]. Our results confirm previous results, which showed that reindeer bone extract has good osteoconductivity both in [5,6,9]. It is known that the animal and fracture models, delivery systems and route of administration influence the dose response in bone healing studies [16].…”
Section: Discussionsupporting
confidence: 88%
“…These amounts healed the defect much better than the controls after eight weeks follow-up. The 10 mg of bone extract group had significantly higher mean stiffness than the collagen group [9]. Our results confirm previous results, which showed that reindeer bone extract has good osteoconductivity both in [5,6,9].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations